Front Cover: Reentrant 2D Nanostructured Liquid Crystals by Competition between Molecular Packing and Conformation: Potential Design for Multistep Switching of Ionic Conductivity (ChemPhysChem 8/2023). Issue 8 (17th April 2023) - Hamaguchi, Kazuma; Lu, Huanjun; Okamura, Shota; Kajiyama, Satoshi; Uchida, Junya; Sato, Shunsuke; Watanabe, Go; Ishii, Yoshiki; Washizu, Hitoshi; Ungar, Goran; Kato, Takashi
Abstract : The Front Cover shows three assembled structures of smectic liquid crystals that show reentrant behavior. More information can be found in the Research Article by Go Watanabe, Goran Ungar, Takashi Kato and co‐workers .